Coronal Balance vs. Sagittal Profile in Adolescent Idiopathic Scoliosis, Are They Correlated? - Ma, Qichao; Wang, Lin; Zhao, Lihua; Wang, Yicheng; Chen, Mengjie; Wang, Sun; Lv, Zhibao; Luo, Yi (Frontiers in Pediatrics, 2020)
Background: Clinical evaluation of the postural balance in adolescent idiopathic scoliosis has been evaluated by coronal and sagittal parameters. The relationship between coronal and sagittal parameters has not been fully studied in adolescent idiopathic scoliosis. Objective: This study aimed to evaluate the relationship between coronal and sagittal parameters in idiopathic scoliosis. Methods: One hundred and three patients of Adolescent Idiopathic Scoliosis (AIS) were recruited. Radiographs were evaluated for the following spine and pelvic measurements. Coronal parameters including thoracic Cobb angle (TC), lumbar Cobb angle (LC), global coronal balance (GCB), apical translation of the major curve (AT), and coronal pelvic tilt (CPT) were analyzed. Sagittal parameters including thoracic kyphosis (TK), lumbar lordosis (LL), sagittal vertical axis (SVA), pelvic incidence (PI), pelvic tilt (PT), and sacral slope (SS) were analyzed. A canonical correlation analysis was performed between all of the coronal parameters and sagittal parameters. Results: One hundred and three patients were recruited (male 15, female 88; aged 12.5 ± 1.5 years). Compared with the published age-matched normal population, TK, PI, LL, and SS were not statistically different in the normal group. However, PT was significantly increased in patent groups (P = 0.003). Canonical correlation analysis showed strong correlation between coronal parameters and sagittal parameters, F(20, 313) = 2.44, p = 0.001. SVA was not correlated with any coronal parameter. Conclusions: Children with AIS showed an increased pelvic tilt sign. In this study, TC, LC, GCB, AT, CPT, TK, LL, SVA, PI, PT, and SS contributed to the postural balance. In AIS, coronal balance is contributed to sagittal balance.